Pengaruh Model Pembelajaran Kontekstual Terhadap Hasil Belajar PAK dan Budi Pekerti Siswa SMP Negeri 1 Siempat Nempu Hulu Kabupaten Dairi - Mei Dewi Simamora; Meditatio Situmorang; Andrianus Nababan; Lince Sihombing; Sabar Rudi Sitompul (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The aim of this research is to determine the effect of the contextual learning model on the PAK learning outcomes of class VIII students at SMP N 1 Siempat Nempu Hulu, Dairi Regency, Academic Year 2023/2024. The method used in this research is a quantitative method with inferential statistical data analysis, by looking at the results of the pre-test and post-test learning. The population is all class VIII students of SMP N 1 Siempat Nempu Hulu for the 2023/2024 academic year, totaling 165 people and a sample of 30 people was determined using the purposive sampling technique. Data collected for variable Y were 15 pre-test and post-test questions, with an overall average score of 88.5>75. The results of data analysis show that there is a positive and significant influence between the contextual learning model on the PAK learning outcomes of class VIII students at SMP N 1 Siempat Nempu Hulu, Dairi Regency, Academic Year 2023/2024.